The relationship between blood albumin and the incidence of preeclampsia in pregnant women - Shodiq, Ja'far; Nurhayati, Etiek; Djohan, Herlinda (ELECTRON (Journal of Science and Technology), 2025)
Maternal Mortality Rate (MMR) is one of the important indicators of public health status. Maternal Mortality Rate (MMR) in West Kalimantan Province was 131 cases. The cause of this maternal mortality rate (22.61%) is hypertension in pregnancy. If pregnant women experience a lack of albumin levels (Hypoalbuminemia) then fetal development will be hampered, it can even cause babies to be born malnourished. Pregnant women who have low albumin levels will have a higher risk of preeclampsia. The purpose of this study was to determine the relationship between blood albumin and the incidence of preeclampsia in pregnant women and examine blood albumin as a risk factor for the incidence of preeclampsia in pregnant women. This research method is descriptive analytic with a cross-sectional approach, The population of this study were pregnant women who performed pregnancy checks at the Tanjungpura University Pratama Clinic. The sampling technique used was Incidental Sampling with a sample size of 43 respondents. The results of the analysis using the Chi-Square test obtained a p-value on Fisher's Exact Test of 0.001 with a sig limit (<0.05). And obtained the odd risk value in the risk estimate table of 20.3. The conclusion of this study shows that there is an association between blood albumin and the incidence of preeclampsia. And blood albumin can be used as a risk factor for the occurrence of preeclampsia in pregnant women.